(untitled) (International Seven Journal of Multidisciplinary, 2024)
The large flow of indigenous refugees/migrants in Brazil represents a range of challenges in the context of social protection. Indigenous women face various forms of historical discrimination, and the situation is aggravated with the migrant and refugee population. This fact results in the exposure of this population to human rights violations in all everyday contexts, impacting civil, political, economic, social, cultural rights, access to justice, as well as the right to a life without violence. The study has as general objective to identify the rights of indigenous Venezuelan women in Brazil. A qualitative descriptive methodology was used, through a bibliographical review through the reading of literary works, articles, theses, and monographs that cover the object of study, as well as IOM Reports in Brazil. It is concluded that there is still much to be done, but, in the context of social assistance, in the analyzed location, the rights of Venezuelan indigenous women are being observed and the implemented actions are being improved.